Oxidative stress resulting from exposure to wood smoke among native women living at high altitude – 3,850 m a.s.l. - Melgarejo-Pomar, Ingrid Gaby (2020)
Objective: To determine the blood levels of two oxidative stress biomarkers among native women exposed to wood smoke living at high altitude (3,850 m a.s.l.). Malondialdehyde (MDA) levels and carboxyhemoglobin (COHb) percentage in venous blood, which is also a cellular hypoxia biomarker, were analyzed. Materials and methods: A descriptive case-series study conducted in 74 women between 14 and 55 years of age exposed to wood smoke and coming from the rural area of the Copacabana Municipality (La Paz, Bolivia) at 3,850 m a.s.l. Screening was carried out through a survey and a complete physical examination. MDA levels and COHb percentage in venous blood were determined, and the demographic variables and transcutaneous oxygen saturation were measured. A descriptive statistical analysis was performed and measures of central tendency were calculated using IBM SPSS Statistics Version 18. Results: Seventy-four (74) women between 14 and 55 years of age were examined. This examination resulted in a mean level of 5.5 μmol/L ± 2 MDA and a median percentage of 1 % COHb (p25 –p75: 0.7 - 1.6). Women who used to burn a mixture of eucalyptus and cow or sheep dung had a higher mean level of MDA and a median percentage of 2.5 % COHb. Conclusions: Indoor air pollution (CAI) due to wood smoke increases the oxidative stress among this native population living at high altitude. This is demonstrated by the increased levels of MDA, and the difference against the biomarker levels of healthy native populations living at high altitude and at sea level. In addition, MDA levels and COHb percentages were higher among women who used to burn a mixture of wood and cow or sheep dung due to the higher harmful effects of such mixture.